REPRODUCTIVE HEALTH OF WOMEN WORKING IN INDUSTRIAL ENTERPRISES AND WAYS TO IMPROVE IT (World Bulletin of Public Health, 2026)
This article examines the reproductive health of women employed in industrial enterprises and analyzes the key factors affecting it. Particular attention is given to the adverse impact of unfavorable working conditions, including exposure to chemicals, industrial dust, noise, vibration, as well as high physical and psycho-emotional stress, which negatively influence the female body, especially the reproductive system. The study also explores methods for assessing reproductive health, as well as the importance of preventive measures and regular medical monitoring. The findings indicate that improving working conditions, optimizing the occupational environment, organizing systematic medical screenings, and promoting a healthy lifestyle are essential for protecting women’s health. In addition, the article proposes comprehensive approaches and practical recommendations aimed at improving reproductive health outcomes among women workers